2004
DOI: 10.7205/milmed.169.9.699
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis in a Soldier Returning from Operation Enduring Freedom

Abstract: This report presents a case of visceral leishmaniasis in a soldier returning from Operation Enduring Freedom. During the United States' last major military conflict, Operation Desert Storm, the diagnosis of multiple cases of visceral leishmaniasis led to policy changes, including a temporary ban on troop blood donation. This case demonstrates the applicability of recently developed Leishmania polymerase chain reaction and serological assays when conventional methods of diagnosis, such as tissue microscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…During 2002 to 2004, more than 500 cases of cutaneous leishmaniasis, caused by L. major, were reported in military personnel stationed in the Middle East and Central Asia 18 . In addition, four cases of visceral leishmaniasis, caused by L. donovani infantum, have been reported from 2002 to 2004 19 . This species has previously been documented to be associated with blood transfusion, although the risk exists for all species.…”
Section: Discussionmentioning
confidence: 99%
“…During 2002 to 2004, more than 500 cases of cutaneous leishmaniasis, caused by L. major, were reported in military personnel stationed in the Middle East and Central Asia 18 . In addition, four cases of visceral leishmaniasis, caused by L. donovani infantum, have been reported from 2002 to 2004 19 . This species has previously been documented to be associated with blood transfusion, although the risk exists for all species.…”
Section: Discussionmentioning
confidence: 99%
“…Immunologically naive individuals from the developed world traveling to areas of endemicity are particularly prone to infection. Leishmaniasis has been found among American soldiers deployed to the Middle East during both Gulf wars, current conflicts in Afghanistan, and Central America (3,7,12,14,18,20,24,29). Civilians traveling into these areas are also at risk (2).…”
mentioning
confidence: 99%
“…Several studies in India and Brazil have concluded that the InBios rapid strip test for diagnosis of VL is highly sensitive and specific (2,9,14), and the U.S. Army currently uses the InBios rapid strip on suspected VL in returning soldiers and on the local Iraq population (3,6,15). The results of these studies and our own demonstrate that the InBios rapid strip has a high sensitivity and specificity for VL detection in multiple countries on different continents, where the species responsible for VL may differ (7).…”
Section: Visceral Leishmaniasis (Vl) Is the Results Of Infection By Thementioning
confidence: 99%
“…The recommended method for diagnosis has been microscopic determination of parasites from bone marrow, splenic, or lymphatic tissue biopsy specimens (7); however, these tests are invasive as well as difficult to perform in rural areas, where VL may be endemic and carry a high risk of complication (6,17). Recently, real-time PCR has been utilized to diagnose Leishmania infection and appears promising; nevertheless, the ability to perform the assay becomes prohibitive in many regions of endemicity with limited medical resources (10,12,16).…”
Section: Visceral Leishmaniasis (Vl) Is the Results Of Infection By Thementioning
confidence: 99%